Normal values for calprotectin in stool samples of infants from the population-based longitudinal born into life study - Peura, Sari; Fall, Tove; Almqvist, Catarina; Andolf, Ellika; Hedman, Anna; Pershagen, Göran; Helmersson-Karlqvist, Johanna; Larsson, Anders (Scandinavian journal of clinical and laboratory investigation, 2018)
Faecal calprotectin is a protein used as a diagnostic marker for inflammatory bowel diseases. We determined upper limits for normal calprotectin values for neonatal, 6, 12 and 24 months old children using a turbidimetric immunoassay in a cohort of Swedish children. The advantage of the method is that opposite to previously used enzyme-linked immunosorbent assay (ELISA) method, it enables measuring single samples, and thus, shortens the analysis time significantly. There were 72 samples (41.7% female) collected neonatally, 63 samples (34.9% female) at 6 months, 60 samples (40.0% female) at 12 months and 51 samples (43.1% female) at 24 months. The upper limits for normal values were 233, 615, 136 and 57 µg mg −1 for infants aged 0, 6, 12 and 24 months, respectively.